Evaluasi Implementasi Epidemiologi Sistem Surveilans Program Kesehatan Ibu dan Anak (KIA) Kabupaten Pangkep: Evaluation Of Surveillance System Epidemiology Implementation Of Mother And Child Health Program (MCH) Pangkep District - Asni Hasanuddin; Fidrotin Azizah; Rony Setianto; Ardiansah Hasin; Hasliani (Pro Health Jurnal Ilmiah Kesehatan, 2023)
Although there is no specific research that documents the effects and economic crisis that hit all countries in the world when the Covid 19 pandemic occurred on pregnancy outcomes, research conducted over three decades shows that it is clear that babies born to mothers who experience CED have an average weight birth weight 2,568 grams or 390.9 grams lower than mothers who do not experience CED. This study aims to determine the weaknesses and needs of the MCH surveillance system in the Pangkep District. Includes methods for collecting MCH surveillance data, analyzing and presenting data, dissemination, and utilization of MCH surveillance data. Based on the results of this evaluation, it can be concluded that the surveillance system for the MCH program in Pangkep Regency is generally running well, some of which still need to be improved are the ability of MCH officers in terms of data analysis, submission of feedback and timely reporting Keywords: Surveillance, Health Program Evaluation, Mother and Child ABSTRAK Krisis ekonomi yang melanda seluruh negara di dunia ssat terjadi pandemi Covid 19 terhadap outcome kehamilan, namun penelitian yang dilakukan dalam tiga tahun terakhir menunjukkan bahwa bayi yang lahir dari ibu yang mengalami KEK mempunyai rata rata berat badan lahir 2.568 gram atau 390,9 gram lebih rendah dibandingkan dengan ibu ang tidak mengalami KEK. Penelitian ini bertujuan untuk mengetahui kelemahan dan kebutuhan sistem surveilans KIA di Kabupaten Pangkep. Meliputi cara pengumpulan data surveilans KIA, pengolahan analisis dan penyajian data, cara penyebarluasan dan cara pemanfaatan data hasil surveilans KIA. Bedasarkan hasil evaluasi tersebut dapat di simpulkan bahwa system surveilans program KIA di Kabupaten Pangkep pada umumnya sudah berjalan baik, beberapa yang masih perlu ditingkatkan adalah kemampuan petugas KIA dalam hal Analisa data, penyampaian umpan balik dan ketepatan waktu pelaporan. Kata kunci: Surveilans, Evaluasi Program Kesehatan, Ibu dan Anak